Micropropagation, Establishment Of Cell Suspension Cultures And Evaluation Of Antioxidant Activities Of Gynura Procumbens - Pan , Lay Pin (2011)

(untitled)
Aseptic bud explants of Gynura procumbens, obtained from the axillary buds of field grown mature plants, could be established via surface-sterilization with 20 % Clorox® for 20 minutes. The formation of multiple shoots could be induced on MS medium supplemented with 2.0 mg/L BA with an average of 14.7 ± 0.7 shoots produced from each bud explant after four weeks of culture. When the concentration of BA supplemented into the MS medium was reduced to 1.5 mg/L BA, reasonably high number of shoots (13.9 ± 1.3 shoots per explant) can still be produced with less production of abnormal shoots.